Estimating Fiscal Multipliers: News From A Non‐linear World. (May 2015) - Caggiano, Giovanni; Castelnuovo, Efrem; Colombo, Valentina; Nodari, Gabriela
<x xml:space="preserve">Abstract</x> We estimate non‐linear VARs to assess to what extent fiscal spending multipliers are countercyclical in the US. We deal with the issue of non‐fundamentalness due to fiscal foresight by appealing to sums of revisions of expectations of fiscal expenditures. This measure of anticipated fiscal shocks is shown to carry valuable information about future dynamics of public spending. Results based on generalised impulse responses suggest that fiscal spending multipliers in recessions are greater than one, but not statistically larger than those in expansions. However, non‐linearities arise when focusing on 'extreme' events, that is, deep recessions versus strong expansionary periods.